Computational assessment of electron density in metallo‐organic nickel pincer complexes for formation of PC bonds. Issue 26 (25th August 2015) - Eller, Joshua J.; Downey, Karen
<x xml:space="preserve">Abstract</x> Hydrophosphination is an atomically efficient method for introducing new carbon‐phosphorous bonds in organic synthesis. New late‐transition metal catalytic complexes are proposed to facilitate this process. These nickel‐based complexes are analyzed using semiempirical (SE), Hartree–Fock (H–F), and density functional theory (DFT) models. H–F proves to be ineffective, while the SE approach has limited, qualitative use. DFT shows electron density at the metal center suitable for catalyzing bond formation in the proposed, reductive hydrophosphination mechanism. It also shows that the pincer complexes under investigation are relatively insensitive to solvent dielectric constant and to the chemical character of the monodentate ligand, both in terms of electron distribution and in terms of molecular orbital energies. © 2015 Wiley Periodicals, Inc.